The Role of Deep Learning in Enhancing Educational Processes: Opportunities and Applications - Susanto, Alpino; Yudianto, Peri; Rahmah, Faridah; Pusvariauwaty, Pusvariauwaty; Handya Putri, Amanda; Suyito, Suyito (eScience Humanity Journal, 2025)
This inquiry endeavors to scrutinize contemporary breakthroughs in the realm of deep learning and their pragmatic utilizations within the educational sphere. To navigate prevailing  impediments, the investigation is executed via a bibliographic examination. The deductions unveil that in recent epochs, artificial intelligence (AI) has undergone an expeditious proliferation. Endeavors formerly deemed exceedingly intricate and formidable for human cognition to unravel are now deftly managed with AI’s intervention. This extraordinary innovation has garnered substantial acclaim owing to its capacity to emulate the cognitive assimilation of the human intellect through neural architectures. Comprehensively, AI is presently categorized into two principal subdivisions: Deep Learning and Machine Learning. Both of these technological paradigms have been instrumental in engendering transformative shifts across multifarious sectors, with particular emphasis on pedagogy. AI-driven mechanisms are increasingly assimilated into scholastic establishments to bolster operational efficacy, curtail expenditures, and cultivate fiscal lucidity by furnishing a perspicuous delineation of monetary inflows and outflows. Furthermore, AI empowers institutions to address exigencies with heightened alacrity and precision, thereby augmenting the overarching caliber of didactic and administrative undertakings. Owing to its extensive promise, AI remains an indispensable domain of inquiry and implementation, with deep learning spearheading its relentless progression.